The Weekend Effect: A Trading Robot and Fractional Integration Analysis - Guglielmo Maria Caporale; Luis A. Gil-Alana; Alex Plastun; Inna Makarenko (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper provides some new empirical evidence on the weekend effect, one of the most recognized anomalies in financial markets. Two different methods are used: (i) a trading robot approach to examine whether or not there is such an anomaly giving rise to exploitable profit opportunities by replicating the actions of traders; (ii) a fractional integration technique for the estimation of the (fractional) integration parameter d. The results suggest that trading strategies aimed at exploiting the weekend effect can generate extra profits but only in a minority of cases in the gold and stock markets, whist they appear to be profitable in most cases in the FOREX. Further, the lowest orders of integration are generally found on Mondays, which can be seen as additional evidence for a weekend effect.
Keywords: G12; C63; 330; efficient market hypothesis; weekend effect; trading strategy